Difference of Some Physiological Indicators Between The Pre- And Post-Phosphagine Anaerobic Stress Phases And Their Contribution To The Muscular Abilities Of The Arms of Young Blinds Fencers (Journal of the College of Basic Education, 2024)
The research aimed to identify the difference in the level of lactic in the blood and the number of breathing times for the stage before and after the phosphagine effort, and the level of muscular capabilities of each of the force (explosive, characterized by speed, and strength endurance) among young blind weapon swordsmen, to identify the relationship and contribution of the difference in the level of lactic acid in the blood and the number of breathing times before and after the phosphagine effort with the muscular capabilities of the arms among young blinds fencers, and adopted the descriptive approach in the style of relational relations, and the limits of the research community were represented by young fencers with shish weapon without The age of (20) years for (17-19) years in Al-Adl Sports Club, with a total number of (11) fencers, who are continuing their training for the sports season (2023/2024), the research sample of them was deliberately selected by a comprehensive inventory method by (100%) of their original community,Conducting physiological and physical tests for them and processing the results with the SPSS system to be the conclusions that the increase in the difference in the level of lactic acid in the blood before and after the phosphagine anaerobic effort is associated with and contributes to increasing the level of types of abilities (explosive, characterized by speed, and force endurance) of the arms of young blinds fencers and affects them directly, and the increase in the level difference in the number of breathing times before and after the phosphagine anaerobic effort is associated with and contributes to increasing the level of types of abilities (explosive, characterized by speed, and strength endurance) of the arms of young blinds fencers and affects The researcher recommended that it is necessary to pay attention to the planning and application of training curricula taking into account the physiological measurement of indicators that express the physiological state of the fencers, especially the difference in the level of lactic acid in the blood before the phosphagine anaerobic effort, Differing in the level of the number of breathing times before the phosphagine anaerobic effort, it is necessary to review the results of physiological and physical tests to track the condition of young fencers and to monitor the appropriateness of their training.